2020
DOI: 10.1159/000510887
|View full text |Cite
|
Sign up to set email alerts
|

Can the Onset of Atrophic Age-Related Macular Degeneration Be an Acceptable Endpoint for Preventative Trials?

Abstract: The slowly progressive nature of age-related macular degeneration (AMD) means that establishing the efficacy of novel preventative treatments aiming to slow progression of disease, remains challenging, and where earlier endpoints are needed to improve their feasibility. This review examines whether the onset of atrophic AMD, as seen as anatomical signs on optical coherence tomography termed nascent geographic atrophy, could act as a useful surrogate endpoint for early intervention trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The finding of this study that regions with nGA showed a lesser extent of visual sensitivity abnormalities than regions with GA on targeted, high-density microperimetry testing is consistent with our previous findings when comparing locations on a standard central microperimetry test that sampled regions with nGA and locations that sampled regions of drusen-associated atrophy on OCT imaging. 12 This finding is also consistent with the notion that nGA represents an earlier stage of the atrophic AMD disease process than GA. 10 , 11 , 14 , 25 The greater degree of visual sensitivity abnormalities detected in eyes with nGA with targeted, high-density microperimetry testing compared with standard central microperimetry testing in eyes with large drusen and without atrophic changes is also similar to our previous observations when comparing test locations that sampled regions with and without nGA using standard central microperimetry testing. 12 This finding is also not unexpected as nGA represents specific signs of photoreceptor degeneration associated with an increased risk of atrophy development.…”
Section: Discussionsupporting
confidence: 86%
“…The finding of this study that regions with nGA showed a lesser extent of visual sensitivity abnormalities than regions with GA on targeted, high-density microperimetry testing is consistent with our previous findings when comparing locations on a standard central microperimetry test that sampled regions with nGA and locations that sampled regions of drusen-associated atrophy on OCT imaging. 12 This finding is also consistent with the notion that nGA represents an earlier stage of the atrophic AMD disease process than GA. 10 , 11 , 14 , 25 The greater degree of visual sensitivity abnormalities detected in eyes with nGA with targeted, high-density microperimetry testing compared with standard central microperimetry testing in eyes with large drusen and without atrophic changes is also similar to our previous observations when comparing test locations that sampled regions with and without nGA using standard central microperimetry testing. 12 This finding is also not unexpected as nGA represents specific signs of photoreceptor degeneration associated with an increased risk of atrophy development.…”
Section: Discussionsupporting
confidence: 86%
“…This goal is achievable with assessments (functional or structural) that reflect how treatments modify causal pathways in AMD progression. 65 , 66 We believe that RMDA has potential of being such a test. We emphasize that our study design is cross-sectional and thus offers insight rather than measured disease progression.…”
Section: Discussionmentioning
confidence: 94%
“…We also recently found that nGA accounted for the observed association between incomplete retinal pigment epithelium and outer retinal atrophy (iRORA)—another recently proposed OCT imaging biomarker for risk of atrophy development 8–11 —and GA development 12 . Collectively, these findings suggested that nGA might be a useful surrogate endpoint for the traditional clinical endpoint of GA 13 …”
Section: Introductionmentioning
confidence: 71%
“…[3][4][5] One previous study reported that the presence of nGA at baseline was associated with a 56-fold increased risk of developing GA in a cohort with an average follow-up duration of approximately 5 years, 6 and we showed in a recent prospective study that nGA was associated with a 78-fold increased rate of developing colour fundus photography (CFP)-defined GA. 7 We also recently found that nGA accounted for the observed association between incomplete retinal pigment epithelium and outer retinal atrophy (iRORA)-another recently proposed OCT imaging biomarker for risk of atrophy development [8][9][10][11] -and GA development. 12 Collectively, these findings suggested that nGA might be a useful surrogate endpoint for the traditional clinical endpoint of GA. 13 Another imaging-based biomarker that may be useful for these purposes is the presence of choroidal signal hypertransmission, which has been observed in the development of atrophic AMD. 3,7,9,14,15 One recent study suggested that the presence of choroidal signal hypertransmission with a greatest linear dimension (GLD) ≥250 μm on an en face sub-retinal pigment epithelium (RPE) slab visualised on an OCT scan pattern with a high transverse resolution (12-μm between B-scans)-termed a 'persistent hypertransmission defect (hyperTD)'-was associated with a significantly increased risk of atrophy development.…”
Section: Introductionmentioning
confidence: 99%